The role of domestic private investment in promoting per capita income convergence amongst ASEAN-5 economies - Hassan, Sallahuddin; Murtala, Musa (2015)
Using data spanning 1980-2014, this study investigates the phenomena of per capita income convergence across a panel of ASEAN-5 economies. The study also delves on the role of domestic private investment in facilitating per capita income convergence amongst the economies.Employing SURADF test to investigate per capita income convergence of the countries to the group average, it was observed that, as opposed to Malaysia and Singapore, economies of Indonesia, Philippines and Thailand tend convergence to the group average. On the impact of gross domestic investment on per capita income convergence, results from system Generalized Method of Moments (GMM) indicate that GDP gap ratio between a pair of economies tend to diminish with a reduction in the gross domestic investment gap ratio between the economies.